Analisis Yuridis Terhadap Wanprestasi Debitur Dalam Perjanjian Kredit Dengan Jaminan Fidusia: Studi Putusan No. 850/PDT.G/2020/PN MDN - Jhonatan ZiusApril Hutabarat; Nurul Afni Octavia; Anggi Sri Haryati Simarmata (Journal of Legal, Political, and Humanistic Inquiry, 2026)
ANALISIS YURIDIS TERHADAP WANPRESTASI DEBITUR DALAM PERJANJIAN KREDIT DENGAN JAMINAN FIDUSIA (Case Study: Putusan No. 850/PDT. This study examines the juridical dimensions of debtor default in credit agreements secured by fiduciary guarantees, with specific reference to Decision Number 850/Pdt.G/2020/PN Mdn. Employing a normative legal research method grounded in statute and case approaches, the analysis focuses on the interpretation of the Indonesian Civil Code and Law Number 42 of 1999 concerning Fiduciary Guarantees, complemented by doctrinal perspectives and relevant jurisprudence. The findings reveal that debtor default manifests not only in the failure to perform contractual obligations but also in the erosion of good faith, which constitutes a fundamental principle in contract law. The study further identifies that dispute resolution mechanisms reflect a structured legal process, yet their implementation remains contingent upon judicial interpretation. Importantly, the court’s refusal to grant fiduciary seizure demonstrates a progressive shift toward balancing creditor rights with debtor protection, particularly in light of constitutional jurisprudence. The analysis underscores the necessity of harmonizing legal certainty with substantive justice through interpretative methods that integrate statutory norms and judicial reasoning. This research contributes to the development of fiduciary law by proposing a more equitable framework for resolving credit disputes in Indonesia. G/2020/PN MDN)